Effects of freshwater input and mariculture (bivalves and macroalgae) on spatial distribution of nanoflagellates in Sungo Bay, China - J Lu (Inter-Research, 2015)
Sungo Bay in northern China has been used for rearing bivalves and macroalgae for several decades. The bivalve culture areas (B-area) are located in the bay head, and the macroalgae culture areas (M-area) are located outside of the B-area. In field investigations, we compared the nanoflagellates (NF) in the B-area and the M-area during 4 seasons. After the field investigations, enclosure experiments were conducted during summer to study the effects of mariculture (bivalves and macroalgae) on NF. In the warm seasons (summer and autumn), during which there was an obvious freshwater input to the bay (especially during summer), NF abundance was negatively related to salinity and was higher in the B-area than in the M-area. In the enclosure experiments, an increase in NF abundance was observed after Day 4 in the bivalve enclosure, but not in the macroalgae enclosure. Considering that the B-area was the area of lower salinity, and the season of largest freshwater input was also the optimal growth season for bivalves, we suggest that the spatial distribution of NF in the warm seasons in Sungo Bay may be influenced by both freshwater input and mariculture.